1983
DOI: 10.1210/jcem-57-4-825
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Luteinizing Hormone, Follicle-Stimulating Hormone, Prolactin, and Their Receptors in Human and Rat Testis Using Immunohistochemistry and Radioreceptor Assay*

Abstract: Immunoperoxidase staining and radioreceptor assay were used to study the localization of LH, FSH, and PRL and their receptors in the human and rat testis. In immunohistochemical staining, the Leydig cells of both species were invariably LH positive and generally FSH negative, but there were some FSH positive cells which were morphologically indistinguishable from the Leydig cells. The tubules were LH negative. The Sertoli cells of both species were FSH positive, whereas the spermatogonia and other germ cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
4

Year Published

1984
1984
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 29 publications
3
38
1
4
Order By: Relevance
“…In accordance, the cells expressing the mutant receptor bound 125 I-labeled rhFSH at only 3% of that measured in cells expressing the wild-type FSHR. The affinity of binding (K a ) was in both cases similar ((4.8-6.7) × 10 9 liter/mol) and in good agreement with the affinity of human testicular FSHR (34). We have recently observed that the mutation mainly affects the folding and trafficking of the receptor protein to the cell membrane (A Rannikko, K Aittomäki, P Pakarinen & I Huhtaniemi, unpublished observations).…”
Section: An Inactivating Mutation Of the Fshr; Hypergonadotropic Ovarsupporting
confidence: 72%
“…In accordance, the cells expressing the mutant receptor bound 125 I-labeled rhFSH at only 3% of that measured in cells expressing the wild-type FSHR. The affinity of binding (K a ) was in both cases similar ((4.8-6.7) × 10 9 liter/mol) and in good agreement with the affinity of human testicular FSHR (34). We have recently observed that the mutation mainly affects the folding and trafficking of the receptor protein to the cell membrane (A Rannikko, K Aittomäki, P Pakarinen & I Huhtaniemi, unpublished observations).…”
Section: An Inactivating Mutation Of the Fshr; Hypergonadotropic Ovarsupporting
confidence: 72%
“…These pathways eventually activate cAMPresponsive element (CRE)-binding protein (CREB), and then transcribe downstream target genes of spermatogenesis. Testosterone is synthesized by Leydig cells upon LH stimulation (de Kretser et al 1971, Wahlstrom et al 1983. Testosterone exerts its biological effects on spermatogenesis via androgen receptors (ARs) that are localized in the Sertoli cells (reviewed in Silva et al (2002)).…”
Section: Hormonal Regulation Of Spermatogenesismentioning
confidence: 99%
“…Клетки Лейдига вырабатывают тестостерон под действием ЛГ, последний оказывает биоло-гическое действие на сперматогенез через андро-геновые рецепторы, расположенные на клетках Сертоли [6]. ФСГ оказывает свое действие через G-ассоциированные рецепторы к ФСГ, находящи-еся на мембране клеток Сертоли.…”
Section: урологические ведомостиunclassified